Enhancing Elementary Students’ Empathetic Awareness through the “Moraka” Candi Jiwa Animated Video - Sinta Maria Dewi; Yuyun Dwi Haryanti; Hesti Widiastuti; Tarpan Suparman; Harmawati (MIMBAR PGSD Undiksha, 2025)
A lack of empathy can negatively impact children's moral and social development in the future. To address this issue, innovative instructional strategies and media are required to foster empathy values from an early age in primary education. This study aims to develop and evaluate the effectiveness of animated video media based on local storytelling to enhance elementary students’ empathetic awareness. The research employed a Research and Development (R&D) approach using the Borg and Gall model. The participants were fifth-grade elementary school students. Data were collected through expert validation, observation, and pretest–posttest assessments, using validation sheets and empathy awareness tests as instruments. The data were analyzed using descriptive and inferential statistics. The expert validation results indicated that the developed animated media is highly suitable for use in learning, in terms of content accuracy, language clarity, visual presentation, and character value integration. The effectiveness test showed a significant improvement in students’ empathy awareness, with a significance value of 0.000 < 0.005. These findings demonstrate that the animated video media is not only effective in fostering empathy but also in integrating local cultural values into character education. The study implies the importance of developing digital learning media that is both contextual and culturally grounded as an alternative approach to strengthening character education at the primary level.